Age of Fear : Othering and American Identity during World War I - Smith, Zachary, 1980- (Book collections on Project MUSE., 2019)
"Why were Americans in 1917 willing to sacrifice so many lives to win a war against a distant enemy? In Age of Fear, Zachary Smith seeks to explain the social and cultural origins of "Anglo-Saxon" American fear of Germans during World War I. He argues that the source of wartime paranoia can be found in Anglo-Americans' deep-seated beliefs of racial and millennial progress--that they were a race facing potential decline and that the once-admired German enemy was a degenerated "Other" posing an existential threat to the United States and Anglo-Saxon identity. This book explores what the Great War meant to a large portion of the American population and provides a historic precedent for modern-day fears of "dangerous" foreign Others. Smith shows that Americans, then as now, have allowed exaggerated fears and overheated rhetoric reduce their ability to accurately calculate the genuine risks of living in the modern world. It is this miscalculation that has fueled American hatred, fear, and disgust toward the country's enemies and led to the surrender of some of American's most sacred and cherished civil liberties for the sake of security"--